2012
DOI: 10.1002/adv.21263
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Irradiated Rubber‐Clay Composites Based on NBR and SBR

Abstract: ABSTRACT:The electrical and thermal properties of gamma-irradiated rubber-clay composites based on acrylonitrile-butadiene rubber (NBR) and styrene-butadiene rubber (SBR) have been performed. The rubber-clay composites were prepared with different ratios of clay up to 50 phr using melt-mixing and hot-pressing methods. The produced sheets were exposed to gamma rays at dose levels in the range from 25 to 250 kGy. The chemical structure was studied by using FTIR technique, whereas thermal stability was tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…By increasing the SBR content, the interfacial area increased up to a certain extent, due to the bulky structure of SBR. On then may point out that a thermodynamic stable system is formed when Δ < 0 [32]. It was found that the in negative values are obtained as the concentration of NBR increases in blends.…”
Section: F Network Characteristics and Physico-chemical Parameters Of Vulcanized Sbr/nbr Blendsmentioning
confidence: 95%
“…By increasing the SBR content, the interfacial area increased up to a certain extent, due to the bulky structure of SBR. On then may point out that a thermodynamic stable system is formed when Δ < 0 [32]. It was found that the in negative values are obtained as the concentration of NBR increases in blends.…”
Section: F Network Characteristics and Physico-chemical Parameters Of Vulcanized Sbr/nbr Blendsmentioning
confidence: 95%
“…By increasing the SBR content, the interfacial area increased up to a certain extent, due to the bulky structure of SBR. On then may point out that a thermodynamic stable system is formed when Δ𝐺 < 0 [32]. It was found that the 𝛥𝐺 in negative values are obtained as the concentration of NBR increases in blends.…”
Section: F Network Characteristics and Physico-chemical Parameters Of...mentioning
confidence: 96%
“…Thus, the explanation of DC conductivity of blend sheets is mainly based on the polarization of tested sheet composition. Furthermore, presence of the electro-negative nitrile groups in NBR which corresponded to interaction and conductivity occurred [28], [32]. As seen, it is clearly detected that the electrical conductivity of the SBR/NBR blends increase with increasing NBR content.…”
Section: G DC Conductivity Of Vulcanized Sbr/nbr Blendsmentioning
confidence: 99%
“…In particular, rubber/clay nanocomposites have attracted great interest in industrial and scientific applications [5,6] due to the remarkable improvement in mechanical properties [7] , electrical and thermal properties [8] , gas permeability [9] , and flame resistance [10] . It is generally accepted that a varying degree of intercalation/exfoliation leads to different reinforcing effects for the rubber/clay nanocomposites [11,12] .…”
Section: Introductionmentioning
confidence: 99%